Impacts of information channels on consumer decision journey: Evidence from an experience durable goods industry - TSAI, Chih-Wei (Institutional Knowledge at Singapore Management University, 2023)
With the emergence of various information technologies, how to reasonably layout in different touch points has become a crucial issue for the company in practice, especially for those experienced durable goods with greater uncertainty and decision complexity. The company seeks to leverage the limited budget to achieve the most efficient marketing strategies, and thus the most effective combination of information channels. On the other hand, consumers could be easily influenced by different information resources in the process of purchase decision-making, and their information search behavior will gradually change with their accumulation of knowledge, experience and distinctive search objectives. Therefore, this paper explores the key question of how different information channels will work in the purchasing decision process of consumers. And I further test the heterogeneity of different types of consumers, and the collaborative effect of different combinations of information channels. Based on consumer decision journey theory and elaboration likelihood model, this paper first analyzes the process of forming consumer brand awareness through peripheral route theoretically. Then, when consumers generate their purchase demand, it will trigger their processing process through central path. And I propose that consumers will use different information channels based on their information-searching objectives in each stage of decision journey, respectively. By leveraging large-scale interviews and surveys data, I verify the important role and contribution distribution of different information channels in each stage of consumer’ decision journey based on rigorous Logit regression and Markov chain method. The empirical results show that, word-of-month is the most influential information channel in the first two stage during consumer decision journey, namely the formation of initial consideration set and active evaluation stage. Besides, digital media is very influential when consumers forming initial consideration set with the second important position; professional recommendation becomes the second influential information channel when consumers approach to active evaluation stage; and offline store plays the most important role when consumers make the final purchase decision. There are heterogeneous effects of information channels among different consumer groups, such as unexperienced consumers are mostly influenced by offline stores in term of brand awareness and evaluation; educated young consumers and less-educated consumers with lower income are easily influenced by recommendations from acquaintances or professionals. And as for the collaborative effect of combinations, digital media, professional recommendations, and offline store are having better effects combined with WOM in stage of initial consideration, active evaluation and final purchase respectively. This paper provides insights for practitioners and makes theoretical contributions on traditional consumer decision journey theory.